A Multi-Island Situation Without the Ocean: Tutors' perceptions about working in isolation from colleagues - Ilse Fouche (Athabasca University Press, 2006)
Distance education is generally seen as a very isolating experience for students, but one often forgets that it can be an equally isolating experience for teaching staff, who sometimes must work in isolation from colleagues. This study examines the experiences of nine tutors at one of the 10 biggest universities in the world, Universtiy of South Africa's (Unisa) Reading and Writing Centres. The tutors all work at different Regional Offices across South Africa. This study examines both quantitative data (closed-ended questions) and qualitative data (open-ended questions) obtained from questionnaires. This study seeks to determine to what extent administrative support, professional development support, and colleague support influence tutors' feelings of isolation. This paper takes the position that if feelings of isolation are curbed, staff retention will be improved, which in turn means that the university retains valuable experience. Findings show that contact with and collaboration between colleagues significantly decrease feelings of isolation. Other important methods of curbing isolation are regular training and continuous administrative support.